DEVELOPMENT OF THE SKHIDNYTSIA TOURISM BRANDIN WARTIME CONDITIONS - PANKIV, Natalia; MOTUZ, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of the peculiarities of the tourism brand of Skhidnytsia in the conditions of the war and the prospects for its development in the post-war period. The work analyzes the essence of the concepts of "brand" and "city branding" and their theoretical and methodological aspects. The history of the formation of the Skhidnytsia tourist brand has been studied. An assessment of the effectiveness of the tourist brand formation of the resort was carried out and the competitive situation in the tourism market in Skhidnytsia was analyzed. The article also examines the impact of the Russian-Ukrainian war on the tourism brand of Skhidnytsia. Proposals have been submitted regarding the positioning of the resort in the future, in particular, the development of rehabilitation and inclusive tourism in Skhidnytsia in the post-war period. Since the full-scale invasion of the Russian Federation on the territory of Ukraine, the resort has become a humanitarian headquarters and shelter for internally displaced persons, which can significantly affect its positioning in the future. However, Skhidnytsia managed to adapt well to new realities and continues to support charitable activities to support Ukraine’s victory in the war. The resort, with its healing mineral waters, has great tourist potential for developing its attractiveness in the tourist market, providing quite high-quality services and services to its visitors. Skhidnytsia has a developed infrastructure for conducting rehabilitation and inclusive programs, as well as highly qualified medical personnel and experienced specialists in the field of tourism. In the past, Skhidnytsia has already functioned as a rehabilitation center for victims of the Chornobyl disaster, and in the future, there may be new buildings for the rehabilitation of military and civilian victims of a full-scale invasion. This can change the identification and positioning of Skhidnytsia in the future, providing opportunities not only for physical but also for spiritual and psychological healing. In general, the development of the Skhidnytsia brand is a complex and long-term process that requires joint efforts on the part of local authorities, businesses, and the community, but with the help of the right development strategy, control, and support from state authorities, it is quite possible to achieve success in this field and ensure the sustainable development of the territory and development.